2010
DOI: 10.1093/schbul/sbq011
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of Paternal Age and Schizophrenia Risk in Male Versus Female Offspring

Abstract: Both APA (≥30) and younger paternal age (<25) increase the risk of schizophrenia; younger paternal age may be associated with an increased risk in males but not females. This risk factor increases the risk of schizophrenia as much as any single candidate gene of risk. The mechanism of these associations is not known and may differ for older and younger fathers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
108
3
5

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(125 citation statements)
references
References 47 publications
9
108
3
5
Order By: Relevance
“…Actually, a study by Malaspina and peers has shown that with each progressing decade of paternal age the risk of schizophrenia almost doubled and by the age of 45 the risk values were tripled in relation to the ones found for younger males [113]. These results were in accordance to several others that likewise confirmed the detrimental effect of APA on schizophrenia risk for the offspring [114]. An additional mental illness linked to APA is the bipolar disorder.…”
Section: Advanced Paternal Age and Offspring Health Complicationssupporting
confidence: 76%
“…Actually, a study by Malaspina and peers has shown that with each progressing decade of paternal age the risk of schizophrenia almost doubled and by the age of 45 the risk values were tripled in relation to the ones found for younger males [113]. These results were in accordance to several others that likewise confirmed the detrimental effect of APA on schizophrenia risk for the offspring [114]. An additional mental illness linked to APA is the bipolar disorder.…”
Section: Advanced Paternal Age and Offspring Health Complicationssupporting
confidence: 76%
“…Several studies have reported higher incidence of neurodevelopmental IVF in vitro fertilization, IVF-ET in vitro fertilization and embryo transfer, GIFT gamete intrafallopian transfer, CI conventional insemination, ICSI intracytoplasmic sperm injection disorders in children with older fathers. Similarly, Miller et al reported a significant association between advanced paternal age and schizophrenia among the offspring by meta-analysis [123]. Advanced paternal age is a risk factor for development of bipolar disorder in children and the highest risk has been reported for children whose fathers were equal and above 55 years old [123].…”
Section: Dna Mutations and Paternal Agingmentioning
confidence: 97%
“…Similarly, Miller et al reported a significant association between advanced paternal age and schizophrenia among the offspring by meta-analysis [123]. Advanced paternal age is a risk factor for development of bipolar disorder in children and the highest risk has been reported for children whose fathers were equal and above 55 years old [123].…”
Section: Dna Mutations and Paternal Agingmentioning
confidence: 97%
“…They have found that advanced paternal age was associated with schizophrenia, and the results were independent from sociodemographic or socioeconomic parameters, family history or early parental death. Meta-analysis of paternal age and schizophrenia risk in male vs. female offspring made by Miller et al 90 revealed that relative risk in the oldest fathers (o50 years) was 1.66 compared with younger fathers. The population attributable risk percentage was 10% for paternal age of .30 years and 5% for paternal age of ,25 years.…”
Section: Schizophreniamentioning
confidence: 99%